2022
DOI: 10.1111/dth.15754
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent bullous pemphigoid and plaque psoriasis successfully treated with Janus kinase inhibitor Baricitinib

Abstract: We report a case of aggressive bullous pemphigoid (BP) concurrent with plaque psoriasis successfully treated with Janus kinase inhibitor Baricitinib. The 83-year-old Chinese man suffered 10 years of psoriasis and developed BP with typical intense blisters and significantly elevated serum anti-BP180 autoantibodies. Due to concerns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The use of JAK inhibition in BP has also been reported by Xiao et al, 8 who successfully treated a patient with psoriasis and BP with the JAK1/JAK2 inhibitor, baricitinib. Elevated expressions of JAK/STAT proteins have been found in lesions of patients with BP and dermatitis herpetiformis, 9 and Xiao et al 8 postulate that the disruption of the JAK/STAT signaling pathway may dampen the autoimmune response in BP, with subsequent reduction in development of bullae. Baricitinib has also been documented to halt the progression of a related disorder, mucous membrane pemphigoid, in a patient who failed other systemic agents.…”
Section: Discussionmentioning
confidence: 67%
“…The use of JAK inhibition in BP has also been reported by Xiao et al, 8 who successfully treated a patient with psoriasis and BP with the JAK1/JAK2 inhibitor, baricitinib. Elevated expressions of JAK/STAT proteins have been found in lesions of patients with BP and dermatitis herpetiformis, 9 and Xiao et al 8 postulate that the disruption of the JAK/STAT signaling pathway may dampen the autoimmune response in BP, with subsequent reduction in development of bullae. Baricitinib has also been documented to halt the progression of a related disorder, mucous membrane pemphigoid, in a patient who failed other systemic agents.…”
Section: Discussionmentioning
confidence: 67%
“…A recent case report suggested a potential for the use of barcitinib, another JAKi, as a novel alternative therapy for concomitant plaque psoriasis and BP, or either condition. 7 Moreover, tofacitinib demonstrated antipruritic effects in other autoimmune skin diseases (atopic dermatitis, psoriasis). 8 , 9 Noteworthily, Juczynska et al found significantly greater expression of JAK/STAT proteins in skin lesions of BP patients compared to controls, 10 which connotes a favorable outcome in targeting this signaling pathway for the treatment of BP.…”
Section: Discussionmentioning
confidence: 99%
“…Results from ongoing clinical trials are thereby necessary to understand the impact of this treatment approach also in BP patients without coexisting psoriasis (58). Inhibition of janus kinase may worth being investigated in BP, since this could allow simultaneous targeting of both IL-4 and IL-23 (59)(60)(61)(62).…”
Section: Experimental Evidence Therapeuticsmentioning
confidence: 99%